2016
DOI: 10.1371/journal.pone.0156967
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Interventions for Families with Parental Cancer and Barriers and Facilitators to Implementation and Use – A Systematic Review

Abstract: BackgroundParental cancer has a significant impact on minor children and families. Psychosocial interventions for affected families can provide support where necessary. This systematic review aims at providing an overview of existing interventions and support programs and focuses on the systematic investigation of barriers and facilitators for using psychosocial interventions for families affected by parental cancer (PROSPERO; registration number CRD42014013020).MethodsA search of five electronic databases (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 57 publications
3
102
0
14
Order By: Relevance
“…A meta-analysis completed in 2016 that analyzed various psychosocial interventions and support systems for parents with cancer and their families reported interventions focused on increasing family communication, enhancing child adjustment, improving mood, and reassuring parenting skills, with no evaluation of the services and no description of any childcare services 24 . Moreover, although interventions were created to provide on-site childcare in clinics for patients undergoing hiv treatment, a home service was never included 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis completed in 2016 that analyzed various psychosocial interventions and support systems for parents with cancer and their families reported interventions focused on increasing family communication, enhancing child adjustment, improving mood, and reassuring parenting skills, with no evaluation of the services and no description of any childcare services 24 . Moreover, although interventions were created to provide on-site childcare in clinics for patients undergoing hiv treatment, a home service was never included 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of psychosocial interventions for families with parental cancer showed that interventions were considered helpful, with improvements in the participants in various outcomes (Inhestern, Haller, Wlodarczyk, & Bergelt, 2016). The interventions were mainly aiming at improving the communication between family members and at supporting children's adaptation to and understanding of cancer, and they consisted of counseling or conversations and were either family centered or person centered (Inhestern et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interventions were mainly aiming at improving the communication between family members and at supporting children's adaptation to and understanding of cancer, and they consisted of counseling or conversations and were either family centered or person centered (Inhestern et al, 2016). The findings also showed that the interventions have to be flexible, easy to access, and offered as a routine care to reach a broader range of families in need of support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations